Platinum nanoparticles decorated on electrodeposited Ti3C2Tx MXene nanosheets as an ultrasensitive biosensor for CA15–3 detection - Sepideh Shafaei; Rahim Mohammad-Rezaei; Balal Khalilzadeh; Ibrahim Isildak (Sensors and Actuators Reports)
In this study, an efficient and ultrasensitive biosensor based on platinum nanoparticles decorated on MXene nanosheets (NSs) was reported for the detection of CA15–3 breast cancer biomarker. In order to increase the accuracy and reproducibility of the fabricated biosensor, MXene NSs and platinum nanoparticles (PtNPs) were electrochemically deposited on the surface of glassy carbon electrode (MXene-Pt/GCE). The synergistic effect of MXene and PtNPs caused an increased conductivity, fast electron transfers, amplified sensitivity and improved stabilization of streptavidin and CA15–3 antibody on the electrode surface. According to the electrochemical results, the electroactive surface area of MXene-Pt/GCE was obtained 0.1345 cm2 which was remarkably more than GCE. The detection limit and linear range for the developed CA15–3 breast cancer biosensor were 1 nU and 1 to 100 nU, respectively. Based on the data, the proposed biosensor exhibited unique reproducibility, stability, and selectivity which can be differentiate between the healthy serum samples and patients suffering from breast cancer.